The effect of two-week L-carnitine supplementation on exercise-induced oxidative stress and muscle damage - Parandak, K.; Arazi, H.; Khoshkhahesh, F.; Nakhostin-Roohi, B. (Asian Journal of Sports Medicine, 2014)
Purpose: This study was conducted to assess the effect of Two-week L-carnitine supplementation on known markers of oxidative stress and muscle damage following acute bouts of exercise in active healthy young men. Methods: Twenty-one active healthy men volunteered for this study. Participants were randomized in a double-blind placebo-controlled fashion into two groups: L-carnitine (C group; n=10) and placebo group (P group; n=11). They arrived at the laboratory after overnight fasting. A baseline blood sample was taken. Afterwards, subjects consumed either L-carnitine (2 capsules containing totally 2000 mg L-carnitine) or placebo (2 capsules containing totally 2000 mg lactose) daily for 14 days. On the day of the test, participants attended the athletics arena after overnight fasting. Then, participants were asked to run 14 km on the track at their highest ability. Blood samples were taken immediately, 2, and 24 hours after exercise. Plasma total antioxidant capacity (TAC), malondialdehyde (MDA) as thiobarbituric acid-reactive substance (TBARS) as a marker of lipid peroxidation, creatine kinase (CK) and lactate dehydrogenase (LDH) as markers of muscle damage were measured. Results: TAC increased significantly 14 days after supplementation and 24h after exercise in C group compared with P group (P<0.05). Serum MDA-TBARS, CK, and LDH were significantly lower 24h after exercise in C group compared with P group (P<0.05). Conclusion: These results suggest that two-week daily oral supplementation of L-carnitine has alleviating effects on lipid peroxidation and muscle damage markers following an acute bout of exercise in active healthy young men.